A Fatal Journey in a Story by Horacio Castellanos Moya - Villalobos Varela, Brenda (2018)
In the story “Variaciones sobre el asesinato de Francisco Olmedo,” the time perspective evolves around the present-past-present continuum. The narrator-protagonist makes a journey in which it is verified that the past represents the kingdom of death, while the present is depicted as paradise. The symbolism reveals that the realm of death (past) is El Salvador, the protagonist’s country of origin, while the United States depicts paradise (present). These relationships lead to a series of socio-ideological implications described in the present analysis.